1998
DOI: 10.1029/98eo00222
|View full text |Cite
|
Sign up to set email alerts
|

Global Positioning System Project to improve Japanese Weather, earthquake predictions

Abstract: The Global Positioning System/Meteorology Project (GPS/MET), a 5‐year project begun in April 1997, will closely monitor atmospheric water vapor over Japan. Using this information, scientists can improve forecasting of catastrophic weather in Japan and also correct transient drifts of a few centimeters per week that occur in estimates of crustal deformation derived from GPS data. Though satellite‐based GPS has become popular for monitoring crustal deformation with mm to cm accuracy, transient drifts, which chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Recent investigations concentrate on the possible use of dense permanent GPS networks as multi-purpose networks providing estimates of atmospheric parameters for weather monitoring and prediction (see, e.g. Naito et al, 1998). In order to verify the results for atmospheric parameters derived from the GPS observations it is necessary to compare them to data from independent measurement techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations concentrate on the possible use of dense permanent GPS networks as multi-purpose networks providing estimates of atmospheric parameters for weather monitoring and prediction (see, e.g. Naito et al, 1998). In order to verify the results for atmospheric parameters derived from the GPS observations it is necessary to compare them to data from independent measurement techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that including more detailed atmospheric moisture data, such as observed total-column precipitable water vapor [hereinafter referred to as precipitable water vapor (PWV)], in numerical model assimilation schemes generally improves model forecast skill (e.g., Naito et al 1998;Gutman and Benjamin 2001;Vedel and Huang 2004). The operational use of surfacebased atmospheric microwave radiometers (e.g., Lesht and Liljegren 1997;Knupp et al 2008) and GPS receivers (e.g., Deblonde et al 2005;Wang and Zhang 2009) now makes it possible to verify a forecast model's atmospheric water vapor field over diurnal temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…The spatiotemporal distribution of tropospheric water vapor is highly variable in summer over the Japanese Islands [e.g., Naito et al , 1998; Iwabuchi et al , 2000] and cannot be properly modeled by a mapping function assuming azimuthal symmetry of the water vapor distribution [e.g., Niell , 1996]. It is hence likely that the fluctuation in GPS time series in summer is due to the deviation of the atmosphere from this idealized state, and it is important to know how and to what extent site coordinates are affected by the unmodeled anisotropy of water vapor distribution.…”
Section: Introductionmentioning
confidence: 99%